Analisis Pengaruh Pelatihan Dan Disiplin Kerja Terhadap Kinerja Melalui Variabel Mediasi Kompetensi Pegawai: Kantor Kesyahbandaran Dan Otoritas Pelabuhan Kelas II Jayapura - Puspawati, Ni Nengah Vera; Syauta, Jack H.; Ratang, Westim (Adhigana Papua: Jurnal Ilmiah Magister Manajemen, 2025)
This study examines the effect of training and work discipline on employee performance, with competency as a mediating variable at the Office of Harbormaster and Port Authority Class II Jayapura. A quantitative approach was employed using Structural Equation Modeling-Partial Least Square (SEM-PLS) with 66 respondents. The findings reveal that training has a positive and significant impact on employee competency, while work discipline also positively and significantly influences competency. Furthermore, employee competency significantly enhances performance. Additionally, both training and work discipline have a direct and indirect positive and significant effect on performance through competency mediation. These results underscore the importance of effective training and work discipline strategies in enhancing employee competency, ultimately contributing to improved organizational performance.